The value of fibroblast growth factor 21 (FGF21) promoter methylation in the repair and regeneration during the course of chronic hepatitis B - Li, Xue; Zhang, Ying; Li, Jihui; Zhao, Tong; Fan, YuChen; Gao, Shuai; Wang, Kai (Frontiers in Cell and Developmental Biology, 2025)
BackgroundHepatitis B virus (HBV) infection continues to pose a significant threat to global public health. The capacity for liver repair and regeneration plays a critical role in maintaining liver homeostasis during HBV infection. This study investigates the impact of FGF21 promoter methylation on liver repair and regeneration in chronic HBV infection.MethodsA total of 216 patients with chronic hepatitis B admitted to the Department of Hepatology, Qilu Hospital, Shandong University from October 2023 to October 2024, along with 15 healthy controls, were included in this study. FGF21 promoter methylation levels in peripheral blood mononuclear cells (PBMCs) were assessed using Methlight. Group comparisons were conducted using the Kruskal–Wallis Test, while Spearman correlation analysis was employed to examine the relationship between FGF21 promoter methylation levels and liver injury, repair, and regeneration in chronic HBV patients.ResultsThe methylation level of the FGF21 promoter in HBeAg(+) CHB patients was significantly lower compared to HBeAg(−) CHB patients and healthy controls. Additionally, HBeAg(+) CHB patients exhibited significantly higher viral loads and more severe liver damage than HBeAg(−) CHB patients. Spearman correlation analysis revealed that the methylation level of the FGF21 promoter in CHB patients was positively correlated with liver repair and regeneration capacity.ConclusionThe methylation level of FGF21 serves as an important biomarker for evaluating liver repair and regeneration ability in patients with HBV. It is closely associated with the extent of liver injury and viral load.